Biophysical and Pharmacological Characterization of Energy-Dependent Efflux of Sb in Laboratory-Selected Resistant Strains of Leishmania (Viannia) Subgenus - Reis, Priscila G. dos; Monte-Neto, Rubens L. do; Melo, Maria N.; Frézard, Frédéric (Frontiers in Cell and Developmental Biology, 2017)
The growing resistance of leishmaniasis to first-line drugs like antimonials in some regions limits the control of this parasitic disease. The precise mechanisms involved in Leishmania antimony resistance are still subject to debate. The reduction of intracellular SbIII accumulation is a common change observed in both laboratory-selected and field isolated resistant Leishmania strains, but the exact transport pathways involved in antimony resistance have not yet been elucidated. In order to functionally characterize the antimony transport routes responsible for resistance, we performed systematic transport studies of SbIII in wild-type and resistant strains of L. (Viannia) guyanensis and L. (V.) braziliensis. Those include influx and efflux assays and the influence of ABC transporters and metabolism inhibitors: prochlorperazine, probenecid, verapamil, BSO and sodium azide. The mRNA levels of genes associated with antimony resistance (MRPA, GSH1, ODC, AQP1, ABCI4 and ARM58) were also investigated in addition to intracellular thiol levels. A strong reduction of Sb influx was observed in L. guyanensis resistant mutant (LgSbR), but not in L. braziliensis (LbSbR). Both mutants showed increased energy-dependent efflux of SbIII, when compared to their respective parental strains. In LgSbR, BSO and prochlorperazine inhibited antimony efflux and resistance was associated with increased MRPA and GSH1 mRNA levels, while in LbSbR antimony efflux was inhibited by probenicid and prochlorperazine in absence of resistance-associated gene modulation. Intracellular thiol levels were increased in both Sb-resistant mutants. An energy-dependent SbIII efflux pathway sensitive to prochlorperazine was clearly evidenced in both Sb-resistant mutants. In conclusion, the present study allowed the biophysical and pharmacological characterization of energy-dependent Sb efflux pathway apparently independent of MRPA, ABCI4 and ARM58 upregulation, in Leishmania (Vianna) mutant selected in vitro for resistance to SbIII. Prochlorperazine has also been identified as an effective chemosensitizer in both Sb resistant mutants, which acts through inhibition of the active efflux of Sb.